The comprehensive review of the neurovascular supply of the ankle joint: Clinical implications - Chirapat Inchai (2020)
© 2020. Anatomy & Cell Biology. The rupture of ligament in the lateral part of ankle joint is a common injury and can lead to chronic ankle instability and lead to ankle osteoarthritis. Ankle arthroscopy is considered as a standard option to treat various ankle problems due to the need for only minimal incisions and fewer complications when compared to open surgery. However, there are complications associated with arthroscopic surgery e.g. damage to the anatomical structures around the portal placement areas. The present review provides anatomical knowledge of the superficial and deep neurovascular structures in the ankle region. These structures are important when ankle surgery is performed in order to avoid any intraoperative injury and prevent any complication following surgery.